EPIDEMIOLOGI MANAJERIAL DAN DETERMINAN SOSIAL PADA SISTEM BPJS: TINJAUAN LITERATUR MODEL EVALUASI KINERJA RS DAERAH BERBASIS TEORI RBV DI TENGAH DINAMIKA KEBIJAKAN DAN KLAIM BPJS PADA RSUD PROVINSI NTB - Ng Phi Shi; Yuly Peristiowati (Bajang Institute, 2026)
Background: The implementation of the National Health Insurance (JKN) by BPJS Kesehatan requires RSUD Provinsi NTB to balance social functions with financial sustainability. Dynamics in claim policies and social determinant pressures often hinder optimal performance. Objective: This study aims to analyze the integration of managerial epidemiology and social determinants into regional hospital performance evaluation models using the Resource-Based View (RBV) theoretical framework. Method: This study employs a Systematic Literature Review (SLR) method. The literature search was conducted via Scopus and Google Scholar databases covering the period 2014-2024. Inclusion criteria focused on articles discussing public hospital management, RBV theory in healthcare, and BPJS policies in Indonesia. Results: Findings indicate that hospital performance amidst BPJS dynamics is significantly determined by internal capabilities (strategic assets) such as claim management information systems and medical coder competencies, aligned with RBV theory. Managerial epidemiology plays a crucial role as a resource allocation predictive tool, while social determinants act as external variables influencing claim risk profiles. Integrating these aspects into performance evaluation is proven to enhance hospital operational resilience. Conclusion: An effective performance evaluation model for regional hospitals must shift from mere financial indicators toward a strategic approach based on internal resource strengths and a deep understanding of local population epidemiological conditions.